Indigenizing the academy : transforming scholarship and empowering communities - Mihesuah, Devon A., 1957-; Waziyatawin (University of Nebraska Press, 2004)
Continuing the thought-provoking dialogue launched in the acclaimed anthology Natives and Academics: Researching and Writing about American Indians, leading Native scholars from diverse disciplines and communities offer uncompromising assessments of current scholarship on and by Indigenous peoples and the opportunities awaiting them in the Ivory Tower. The issues covered are vital and extensive, including how activism shapes the careers of Native academics; the response of academe and Native scholars to current issues and needs in Indian Country; and the problems of racism, territoriality, and ethnic fraud in academic hiring. The contributors offer innovative approaches to incorporating Indigenous values and perspectives into the research methodologies and interpretive theories of scholarly disciplines such as psychology, political science, archaeology, and history and suggest ways to educate and train Indigenous students. They provide examples of misunderstanding and sometimes hostility from both non-Natives and Natives that threaten or circumscribe the careers of Native scholars in higher education. They also propose ways to effect meaningful change through building networks of support inside and outside the Native academic community. Designed for classroom use, Indigenizing the Academy features a series of probing questions designed to spark student discussion and essay-writing.
Keywords: Indians of North America -- Education (Higher); Indians of North America -- Historiography.; Indians of North America -- Research.; Discrimination in higher education -- United States.; Educational equalization -- United States.; Indian teachers -- Employment -- United States.; Education -- Social aspects -- United States.; Education and state -- United States.; Discrimination dans l'enseignement supérieur -- États-Unis.; Démocratisation de l'enseignement -- États-Unis.; Enseignants des Peuples autochtones -- Travail -- États-Unis.; Éducation -- Politique gouvernementale -- États-Unis.; EDUCATION -- Higher.; Discrimination in higher education; Education and state; Education -- Social aspects; Educational equalization; Indians of North America -- Historiography; Indians of North America -- Research; United States